Analisis Determinan Pengeluaran Konsumsi Rumah Tangga Masyarakat Miskin di Kabupaten Aceh Utara - Khairil Anwar (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The Method that used to analyze the data is Multiple Linear Regression model, specified in Least Square Dummy Variable (LSDV) method. The estimation result found that all of independent variable positive significantly influenced the food consumption. Otherwise, the negative ones significantly influenced the non-food consumption outcome. The estimation result also found that the level of consumption for many kinds of urban food was fewer than hinterland society food consumption about Rp12.046,94. However, the urban consumption more excessively than coastal area society about Rp13.238,54. While the level of consumption outcome for many kinds of non-food urban consumption larger than non-food hinterland consumption about Rp57.045,73. Also larger than non-food coastal society consumption about Rp31.760,25. The variation of independent variable capability to explain the food consumption about 92,5% and nonfood consumption outcome about 87,4%. The specification models were appropriated which the model free of multicollinierity and Heteroscedasticity classic assumption collision. The result of this research was expected to be a good suggestion to the North Aceh Government and related department to arrange the planning and implementing the development policy, especially to improve the life level of poor society, and could be a guidance for poorness decreasing in North Aceh Regency.Keywords: consumption, income, social-economy, poverty